ANALISIS SEMANTIK CERITA LAKIPADADA (Semantics Analysis of Lakipadada Story) - Jusmianti Garing (Balai Bahasa Sulawesi Selatan, 2017)
Toraja reserved the complexity of the language, literature, and unique culture. However, the complexity indeed contributed positive impact towards Toraja people’s life in the past, present, and future. Toraja language itself has the different structure with existing languages and has complex meaning, as well as on literature and culture. The research discussed the semantic analysis of Lakipadada story as a part of the literature and culture of Torajanese. The purpose of this research is to describe semantics in Lakipadada story qualitatively-descriptive. The primary data (oral data) is utterances of Toraja language, namely words, phrases, and sentences obtained through an interview, note, and record technique. The source of data (written data) is gained from the book ‘Cerita Lakipadada’ (Lakipadada story). The result shows that the meaning contained in the Lakipadada story is lexical meaning, grammatical meaning, figurative meaning, and proverb meaning. Those semantic elements result denotation meaning, connotation meaning, referential meaning, intransitive meaning, progressive meaning, simile/supposition meaning, and philosophical meaning. The meanings reflect the life of Torajanese people who have polite language and unique culture.abstrakToraja menyimpan kompleksitas bahasa, sastra, dan budaya yang unik. Namun, kompleksitas tersebut justru memberikan dampak positif terhadap kehidupam masyarakat Toraja dulu, kini, dan akan datang. Bahasa Toraja sendiri memiliki struktur bahasa yang berbeda dengan bahasa-bahasa yang ada dan memiliki makna yang kompleks, begitupun terhadap sastra dan budayanya. Penelitian ini membahas mengenai semantik dalam cerita rakyat Toraja ‘Lakipadada’ sebagai bagian dari sastra dan budaya masyarakat Toraja. Tujuan penelitian ini adalah mendeskripsikan makna atau semantik dalam cerita rakyat Lakipadada secara kualitatif berdasarkan data lapangan. Data primer berupa tuturan bahasa Toraja dalam bentuk kata, frasa, dan kalimat. Sumber data diperoleh dari buku mengenai ‘Cerita Lakipadada’. Hasil penelitian menunjukkan bahwa makna yang terdapat dalam cerita rakyat Toraja ‘Lakipadada’ adalah makna leksikal, makna gramatikal, makna kias, dan pepatah. Unsur-unsur semantik tersebut menghasilkan makna denotasi, konotasi, makna yang berdasarkan referensinya, makna intransitif, makna progresif, makna perumpamaan, dan makna filosofis. Makna-makna tersebut mencerminkan kehidupan masyarakat Toraja yang memiliki bahasa santun dan budaya unik.